(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
In the conditions of the Bukhara region of the Peshku district, cotton is damaged by more than 200 types of pests. Among them, the most common is the winter cutworm, the harmfulness of which reaches 18%. To save cotton from damage by the winter scoop, a complex system of measures is used, among which the leading place is occupied by agrotechnical and chemical methods of control.